Nilai Pendidikan Islam dalam Tradisi Awiq-Awiq Pisuke Pada Pernikahan Adat Masyarakat Lombok (Studi Kasus di Desa Aik Ampat Bawak Gunung) - Riky Supratama (At Turots: Jurnal Pendidikan Islam, 2024)
One of the most important events in human life is marriage. Marriage is very important to the Saak society, as is the society in general, especially since the majority of the population is Muslim, whose teachings strongly advocate marriage. A tribe that is the focus of research in terms of its customary marriage system. In a marriage or marriage, the community of the mines is known as one of the customs that must exist whenever there is marriage. This custom is called pisuke, which is meant to be an out-of-the-board gift to the female side. In this study the author wanted to study the values of Islamic education contained in the Lombok marriage tradition called the awiq-awiq pisuke tradition. The method used in this writing is the method of qualitative writing. This research uses historical, anthropological and normative approaches. There are four values of Islamic education that researchers find in the Pisuke tradition that the researchers carefully investigate. Among them are the values of worship, equality values, character values and help values.